DETERMINANTS OF PATIENT SATISFACTION ON INTERIOR DESIGN QUALITY OF PUBLIC HOSPITALS IN MALAYSIA - Shariffah Syafiqah Aljunid; Nurul Nabilah Huda Mohamad Shukri; Mohd Zafrullah Mohd Taib; Zanariah Abu Samah (Malaysian Journal of Public Health Medicine, 2020)
Being in a hospital can be a stressful experience especially to the patients. The importance of design quality as a trigger to patients' satisfaction is becoming a topic of significant relevance as it also impacts the building operation. This study aims to determine the factors influencing the patients' satisfaction toward the interior design quality of inpatient units at public hospitals in Malaysia. Self-administered questionnaires were distributed among 483 inpatients from 5 Obstetrics and Gynaecology wards at public hospitals in the Klang Valley region. The Structural Equation Model (SEM) technique was applied to examine the causal relationship and to test the hypothesis of the patients' satisfaction toward the interior design quality. The results revealed that space planning (? = 0.265), lighting (? = 0.263), furniture (? = 0.243), and color (? = 0.138) have a significantly positive effect on patients' satisfaction toward the interior design quality. Whereas way-finding, safety, air quality and accessibility have no significant effect on the patients' satisfaction. This study concludes that certain qualities of interior design have great impact on patients' satisfaction. The findings proved that revamping the inpatient units' space planning can lead to significant patient experience improvements, while the aspect of accessibility is the least concern to the patients when they stay in the hospital. This study provides input to help designers, architects and hospital planners to evaluate their priorities in planning and designing better hospitals in the future.